2015
DOI: 10.1002/app.43249
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous improvement in strength, toughness, and thermal stability of epoxy/halloysite nanotubes composites by interfacial modification

Abstract: This work investigated the effect of silane modification of halloysite nanotubes (HNTs) on the mechanical properties of epoxy/HNTs nanocomposites. Three kinds of silane coupling agents, including 3-(2-aminoethyl)-aminopropyltrimethoxysilane (AEAPS), (3-glycidyloxypropyl)-trimethoxysilane (GPTMS), and octyltriethoxysilane (OTES), were employed. It was shown that the modified HNTs exhibited a better dispersion in the epoxy matrix compared with pristine one. Because of strong interfacial interaction between AEAPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 45 publications
1
29
0
Order By: Relevance
“…(A). The characteristic peaks of p‐HNTs at 3694 and 3621 cm −1 , 1083 and 1031 cm −1 , 1114 and 796 cm −1 corresponding to inner‐surface Al&bond;OH stretching bands, in‐plane Si&bond;O stretching, apical Si&bond;O stretching and Si&bond;O&bond;Si symmetric stretching, respectively, are also observed in the spectra of h‐HNTs, indicating that surface treatment with different NaOH concentrations has no effect on the peak position and intensity of bands. Furthermore, it is hard to detect the obvious variation of hydroxyl content using different NaOH solution treatment in the FTIR spectra due to structural complexity of HNTs.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…(A). The characteristic peaks of p‐HNTs at 3694 and 3621 cm −1 , 1083 and 1031 cm −1 , 1114 and 796 cm −1 corresponding to inner‐surface Al&bond;OH stretching bands, in‐plane Si&bond;O stretching, apical Si&bond;O stretching and Si&bond;O&bond;Si symmetric stretching, respectively, are also observed in the spectra of h‐HNTs, indicating that surface treatment with different NaOH concentrations has no effect on the peak position and intensity of bands. Furthermore, it is hard to detect the obvious variation of hydroxyl content using different NaOH solution treatment in the FTIR spectra due to structural complexity of HNTs.…”
Section: Resultsmentioning
confidence: 98%
“…firstly use piranha solution (a mixture of H 2 SO 4 and H 2 O 2 ) to hydroxylate most of the surface of HNTs, which had higher activity for silanization . Wang and co‐workers further found that silane modification of hydroxylated HNTs firstly treated with NaOH solution could obviously improve the mechanical strength and toughness simultaneously . However, previous studies of surface‐hydroxylated HNTs had only emphasized the use of NaOH solution treatment to increase the hydroxyl content.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer composites compose of filler and polymer matrix like thermoplastic, thermoset and elastomer [7]. Epoxy resins (ERs) are one of the most important thermoset matrices due to their remarkable properties including good mechanical and electrical strength [8], excellent adhesion capacity, high thermal and chemical resistance, low shrinkage [9] and processability [10]. In spite of these advantages, ERs have some adverse properties such as low thermal conductivity [11], high flammability [12] and brittleness [13] that restrict their applications.…”
Section: Introductionmentioning
confidence: 99%
“…Epoxy resins are types of widely used thermosetting polymers because of their high strength and stiffness, excellent chemical and thermal resistance; however, they are intrinsically fragile which limits their use. Inorganic nanofillers are often employed to improve the toughness of epoxy resin since these fillers can increase the toughness without sacrificing its rigidity and thermal properties . When chosen as matrix for glass and carbon fibers composites due to its excellent suitability for various processing techniques, the intrinsic brittleness of the matrix has greatly restricted their applications .…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have been made in order to improve the nanodispersion of HNT expecting an improvement in the matrix toughening. On the one hand, different mixing methods have been reported, like mechanical agitation, ball milling, ultrasonic treatments, solvent assistance, and so forth. On the other hand, there are strategies oriented to improve the filler–matrix physicochemical interaction through the surface modification of the halloysite .…”
Section: Introductionmentioning
confidence: 99%